Comparison of lower limb kinetics during vertical jumps in turnout and neutral foot positions by classical ballet dancers - Imura, A.; Iino, Y. (Sports Biomechanics, 2017)
The purpose of this study was to investigate the effect of hip external rotation (turnout) on lower limb kinetics during vertical jumps by classical ballet dancers. Vertical jumps in a turnout (TJ) and a neutral hip position (NJ) performed by 12 classical female ballet dancers were analysed through motion capture, recording of the ground reaction forces, and inverse dynamics analysis. At push-off, the lower trunk leaned forward 18.2° and 20.1° in the TJ and NJ, respectively. The dancers jumped lower in the TJ than in the NJ. The knee extensor and hip abductor torques were smaller, whereas the hip external rotator torque was larger in the TJ than in the NJ. The work done by the hip joint moments in the sagittal plane was 0.28 J/(Body mass Height) and 0.33 J/(Body mass Height) in the TJ and NJ, respectively. The joint work done by the lower limbs were not different between the two jumps. These differences resulted from different planes in which the lower limb flexion-extension occurred, i.e. in the sagittal or frontal plane. This would prevent the forward lean of the trunk by decreasing the hip joint work in the sagittal plane and reduce the knee extensor torque in the jump. ABSTRACT FROM AUTHOR